Gaya Kepemimpinan Prof. Dr. Kh. Asep Saifuddin Chalim dalam Meningkatkan Motivasi Kerja Karyawan di Pesantren - Heriyono Heriyono; Rudolf Chrysoekamto; Rezki Nurma Fitriah; Ari Kartiko (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2021)
The Amanatul Ummah Islamic Boarding School is an educational institution for Islamic boarding schools located at the foot of Mount Welirang, and has several institutions, including superior MTS, superior MA, and Superior Universities. The formulation of the research problem is how the leadership style is applied by Kiai and what forms of motivation are applied to employees at the Amanatul Ummah Islamic Boarding School. With this type of field research (field research) qualitative, with research subjects are Kiai, employees and partners, data collection by observation, interview and documentation techniques. The data analysis used according to Miles Huberman consists of data reduction, data presentation and conclusion drawing, using data validity techniques, triangulation of data sources and triangulation of data collection, so that the resulting data is accurate. From the results of this study, Kiai Pondok Pesantren Amantul Ummah does not only apply one leadership style but also applies a different leadership style. The leadership style applied is dominant with authoritarian leadership, although on the other hand he also applies charismatic leadership. This is reinforced by the leadership function implemented by the Kiai Pondok Pesantren Amanatul Ummah. And the forms of motivation given by Kiai are establishing good personal relationships with employees and work partners, paying attention to employee welfare, giving rewards to employees who excel, gathering and evaluating together with employees.